2014
DOI: 10.3390/e16020870
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and Crackling Noise of AlxNbTiMoV High Entropy Alloys

Abstract: A series of high entropy alloys (HEAs), Al x NbTiMoV, was produced by a vacuum arc-melting method. Their microstructures and compressive mechanical behavior at room temperature were investigated. It has been found that a single solid-solution phase with a body-centered cubic (BCC) crystal structure forms in these alloys. Among these alloys, Al 0.5 NbTiMoV reaches the highest yield strength (1,625 MPa), which should be attributed to the considerable solid-solution strengthening behavior. Furthermore, serration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
46
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(63 citation statements)
references
References 31 publications
12
46
1
4
Order By: Relevance
“…The large mixing entropy may benefit the phase stabilization at high temperatures for potential applications as high-temperature alloys [1]. Several single-phase HEA have been reported in the literature, including face-centered cubic (fcc) CrCoFeMnNi [2] and CoCrFeNiAl 0.1 [3] as well as body-centered cubic (bcc) NbMoTaW [4], NbMoTaVW [5], NbTiMoVAl 0.5 [6] and HfNbTaTiZr [7] refractory alloys. The addition of non-equiatomic Al has been found to benefit the strength and oxidation resistance of HEA [8], but often leads to complex microstructure evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The large mixing entropy may benefit the phase stabilization at high temperatures for potential applications as high-temperature alloys [1]. Several single-phase HEA have been reported in the literature, including face-centered cubic (fcc) CrCoFeMnNi [2] and CoCrFeNiAl 0.1 [3] as well as body-centered cubic (bcc) NbMoTaW [4], NbMoTaVW [5], NbTiMoVAl 0.5 [6] and HfNbTaTiZr [7] refractory alloys. The addition of non-equiatomic Al has been found to benefit the strength and oxidation resistance of HEA [8], but often leads to complex microstructure evolution.…”
Section: Introductionmentioning
confidence: 99%
“…There are, in fact, only a few HEAs with a true single-phase face-centered cubic (fcc) [13,14], body-centered cubic (bcc) [15][16][17][18] or hexagonal close-packed (hcp) [19] structure, in which the high-entropy effect dominates. Among them, the equiatomic fcc-NiFeCoCrMn alloy [13] is a prominent example that exhibits high phase stability, and its mechanical properties and microstructure have been studied [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in this area have demonstrated many exciting properties, such as the high hardness retention up to 800°C, [1][2][3] high yield strengths at elevated temperatures, [4] high corrosion resistance to acids, [5,6] high fatigue and fracture resistance, [7,8] desirable balance of magnetic and mechanical properties, [8][9][10][11][12] etc. However, to date, elemental segregation and phase decomposition are quite common in many 'claimed' bulk HEAs, such as Cu segregation, [1] Cr segregation, [13,14] Ni-Al precipitation, [15] Ti-Al precipitation, [16,17] and spinodal decomposition of ordered and disordered phases [2,18] due to the negative mixing enthalpy of these elements. [19] *Corresponding author.…”
mentioning
confidence: 99%